The liver-resident immune cell repertoire - A boon or a bane during machine perfusion? - Fodor, M.; Salcher, S.; Gottschling, H.; Mair, A.; Blumer, M.; Sopper, S.; Ebner, S.; Pircher, A.; Oberhuber, R.; Wolf, D.; Schneeberger, S.; Hautz, T. (Frontiers in Immunology, 2022)
The liver has been proposed as an important “immune organ” of the body, as it is critically involved in a variety of specific and unique immune tasks. It contains a huge resident immune cell repertoire, which determines the balance between tolerance and inflammation in the hepatic microenvironment. Liver-resident immune cells, populating the sinusoids and the space of Disse, include professional antigen-presenting cells, myeloid cells, as well as innate and adaptive lymphoid cell populations. Machine perfusion (MP) has emerged as an innovative technology to preserve organs ex vivo while testing for organ quality and function prior to transplantation. As for the liver, hypothermic and normothermic MP techniques have successfully been implemented in clinically routine, especially for the use of marginal donor livers. Although there is evidence that ischemia reperfusion injury-associated inflammation is reduced in machine-perfused livers, little is known whether MP impacts the quantity, activation state and function of the hepatic immune-cell repertoire, and how this affects the inflammatory milieu during MP. At this point, it remains even speculative if liver-resident immune cells primarily exert a pro-inflammatory and hence destructive effect on machine-perfused organs, or in part may be essential to induce liver regeneration and counteract liver damage. This review discusses the role of hepatic immune cell subtypes during inflammatory conditions and ischemia reperfusion injury in the context of liver transplantation. We further highlight the possible impact of MP on the modification of the immune cell repertoire and its potential for future applications and immune modulation of the liver.